2015
DOI: 10.1038/mt.2015.122
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Neuronal Preferential Systemic Gene Therapy for Neurotransmitter Deficiency

Abstract: Aromatic L-amino acid decarboxylase (AADC) deficiency is a rare autosomal recessive disease that impairs synthesis of dopamine and serotonin. Children with AADC deficiency exhibit severe motor, behavioral, and autonomic dysfunctions. We previously generated an IVS6+4A>T knock-in mouse model of AADC deficiency (Ddc(KI) mice) and showed that gene therapy at the neonatal stage can rescue this phenotype. In the present study, we extended this treatment to systemic therapy on young mice. After intraperitoneal injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Due to concerns that this hyperactivity may have been due to excess ectopic DA production and the invasive procedure in the neonatal period, we modified our viral vector delivery strategy to use intraperitoneal injection of the neuronal preferential viral vector (yfAAV9/3‐Syn‐I‐mAADC) in 7‐day‐old DDC KI mice (Lee et al, ). The yfAAV9/3‐Syn‐I‐mAADC‐treated mice showed greater neuronal transduction, higher brain DA level and less hyperactivity compared with AAV9‐CMV‐hAADC‐treated mice (Lee et al, ). Further large animal experiments are in progress to develop the next generation of gene therapies for patients with AADCD.…”
Section: Developing Other Therapeutic Strategiesmentioning
confidence: 99%
“…Due to concerns that this hyperactivity may have been due to excess ectopic DA production and the invasive procedure in the neonatal period, we modified our viral vector delivery strategy to use intraperitoneal injection of the neuronal preferential viral vector (yfAAV9/3‐Syn‐I‐mAADC) in 7‐day‐old DDC KI mice (Lee et al, ). The yfAAV9/3‐Syn‐I‐mAADC‐treated mice showed greater neuronal transduction, higher brain DA level and less hyperactivity compared with AAV9‐CMV‐hAADC‐treated mice (Lee et al, ). Further large animal experiments are in progress to develop the next generation of gene therapies for patients with AADCD.…”
Section: Developing Other Therapeutic Strategiesmentioning
confidence: 99%
“…We previously demonstrated that Ddc KI (KI) mice exhibit a profound DA deficiency, poor weight gain, and early death (Lee et al, 2013); possibly due to reduced food intake and followed by essential compounds deficiency including tryptophan that further worsen the serotonin deficiency; and gene therapy rescues these deficits (Lee et al, 2014, 2015). Gene therapy-treated and untreated mice were used in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…One possible reason for the restoration may be associated with an increment in dopamine level in the brain. Furthermore, we have previously reported that gene therapy is effective and improves motor function in patient and mouse with AADC deficiency (Hwu et al, 2012; Lee et al, 2014, 2015). These results suggest that replenished dopamine level in the brain by gene therapy restored motor function and cellular homeostasis in AADC deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent clinical trial (#NCT01395641) of AADC deficiency, Hwu et al directly injected AAV2 vector carrying AADC gene into the bilateral putamen of four 4- to 6-year-old patients. 78 , 79 All subjects were reported to gain weight after 3 to 6 months post-gene transfer and had better head control and emotional stability. Importantly, their Alberta Infant Motor Scale, Peabody Developmental Motor Scale, and Comprehensive Developmental Inventory for Infants and Toddlers scores were better after 15 to 24 months of gene therapy, indicating improvement in their motor and cognitive functions.…”
Section: Inherited Neurological Disordersmentioning
confidence: 98%